Seven psychopaths - McDonagh, Martin; Farrell, Colin, 1976-; Rockwell, Sam; Walken, Christopher, 1943- (Culver City, Calif. : Sony Pictures Home Entertainment, 2013)
A screenwriter struggling for ideas suddenly finds a story when his odd friend Billy shows up at his door with a small dog he kidnapped from a gangster.
Originally released as a motion picture in 2012.
Features: Seven psychocats, Martin McDonagh'S Seven psychopaths, Crazy locations, Woody Harrelson is Charlie, Colin Farrell is Marty, Layers, UltraViolet enabled.
Colin Farrell, Sam Rockwell, Christopher Walken, Michael Pitt, Michael Stuhlbarg, Abbie Cornish.
MPAA rating: R.
DVD, Dolby digital 5.1.
In English with optional English or Spanish subtitles.
Keywords: Screenwriters -- Drama; Gangsters -- Drama; Criminal behavior -- Drama; Dogs -- Drama; Crime films; Fiction films; Video recordings for the hearing impaired; Feature films; Comedy films